2008
DOI: 10.1136/tc.2007.022426
|View full text |Cite
|
Sign up to set email alerts
|

PREP advertisement features affect smokers’ beliefs regarding potential harm

Abstract: Background The Institute of Medicine report on potential reduced exposure products (PREPs) recommends that advertising and labelling be regulated to prevent explicitly or implicitly false or misleading claims. Belief that a product is less harmful may increase use or prevent smoking cessation. Objective To determine the effect of altering advertisement features on smokers’ beliefs of the harm exposure from a PREP. Methods A Quest advertisement was digitally altered using computer software and presented to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
(25 reference statements)
0
30
1
Order By: Relevance
“…A nationally representative survey of smokers found that over half believed that LNCs were less dangerous than regular cigarettes (Cummings et al, 2004). Further, an experimental study (Strasser et al, 2008) found that smokers assigned to view ads for one brand of LNCs believed them to be healthier and safer, and believed that switching to them could reduce exposure to tar, carcinogens, and other chemicals. Another study found that smokers believed LNCs to be associated with a lower risk of lung cancer, other cancers, emphysema, bronchitis, heart disease, and stroke (Hatsukami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A nationally representative survey of smokers found that over half believed that LNCs were less dangerous than regular cigarettes (Cummings et al, 2004). Further, an experimental study (Strasser et al, 2008) found that smokers assigned to view ads for one brand of LNCs believed them to be healthier and safer, and believed that switching to them could reduce exposure to tar, carcinogens, and other chemicals. Another study found that smokers believed LNCs to be associated with a lower risk of lung cancer, other cancers, emphysema, bronchitis, heart disease, and stroke (Hatsukami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found in another survey that interest in PREPs was associated with non-health-related factors, including favorable attitudes toward technology and a willingness to experiment with new products and trends ( Parascandola, Hurd, & Augustson, 2008 ). Nevertheless, several previous studies have found that advertising messages for PREP-type products can infl uence smokers ' beliefs regarding potential harm ( Hamilton et al, 2004 ;O'Connor et al, 2007 ;O'Hegarty, Richter, & Pederson, 2007 ;Shiffman et al, 2007 ;Strasser, Tang, Tuller, & Cappella, 2008 ). Thus, further study is warranted here to better understand consumers ' expectations and health beliefs about PREP products under different conditions.…”
Section: Discussionmentioning
confidence: 90%
“…Consistent with previous work (Lochbuehler et al, 2016; Shadel et al, 2006; Strasser et al, 2012; Strasser et al, 2008), participants viewed an unaltered company-created advertisement for 30 seconds (Strasser et al, 2008), deliberately presented five days before randomization to approximate real-world conditions (e.g., viewing novel product advertisement in a magazine/online/etc., then purchasing it the next time at store; i.e., not immediately after viewing advertisement).…”
Section: Methodsmentioning
confidence: 88%
“…Eight items (Lochbuehler et al, 2016; Shadel et al, 2006; Strasser et al, 2008) rated on a 5-point response scale (1= “definitely untrue”, 5=“definitely true”) assessed participants’ Quest cigarette beliefs only at the initial study visit, before and after viewing the advertisement: “Quest cigarettes:” (a) “are lower in nicotine than regular cigarettes”, (b) “are lower in tar than regular cigarettes”, (c) “are less addictive than regular cigarettes”, (d) “are less likely to cause cancer than regular cigarettes”, (e) “have fewer chemicals than regular cigarettes”, (f) “healthier than regular cigarettes”, (g) “make smoking safer”, (h) “help people quit smoking.” Items b–h were summed to create a cumulative false beliefs variable (Cronbach’s α’s = 0.77 and 0.81 for pre- and post-advertisement variables, respectively); consistent with previous work (Lochbuehler et al, 2016; Shadel et al, 2006), the first item was excluded because it was factually correct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation